Building Bridges to Enhance Degree and Career Opportunities - Deborah A. Greenawald Ph.D., RN; Karen S Thacker Ph.D, RN; Samuel M Bradley DBA; Thomas Franek Ph.D, ATC; Thomas Porrazzo Ph.D., ATC; Christopher Wise DPT, Ph.D (c), PT (Academic Chairpersons Conference Proceedings, 2020)
External pressures on higher education are challenging universities to focus on preparing graduates with more broadly designed curricula that contain translatable skills and include interdisciplinary knowledge. In this presentation, the process of identifying and creating new academic programs based on unique student goals and contemporary employment needs will be discussed.
Keywords: Interdisciplinary; Collaborative teaching; Curricular flexibility; Retention enhancement; Transferable learning skills